Correction: Stable group 8 metal porphyrin mono- and bis(dialkylcarbene) complexes: synthesis, characterization, and catalytic activity. Issue 22 (1st June 2020) - Wang, Hai-Xu; Wan, Qingyun; Low, Kam-Hung; Zhou, Cong-Ying; Huang, Jie-Sheng; Zhang, Jun-Long; Che, Chi-Ming
Abstract : Correction for 'Stable group 8 metal porphyrin mono- and bis(dialkylcarbene) complexes: synthesis, characterization, and catalytic activity' by Hai-Xu Wang et al., Chem. Sci., 2020, 11, 2243–2259, DOI: ; 10.1039/C9SC05432D .